Resistance mechanisms matter in SIR models - Timothy C. Reluga; Jan Medlock (Mathematical Biosciences and Engineering)
We compare four SIR-style modelsdescribing behavioral or immunological disease resistance thatmay be both partial and temporaryin parameter regions feasible for interpandemic influenza.For the models studied, backward bifurcations andbistability may occur in contexts where resistance isdue to behavior change, but they do not occur when resistanceoriginates from an immune response. Care must be exercisedto ensure that modeling assumptions about resistance areconsistent with the biological mechanisms under study.